Effect of palady and cup feeding on premature neonates′ weight gain and reaching full oral feeding time interval - Maryam Marofi; Fatemeh Abedini; Majid Mohammadizadeh; Sedigheh Talakoub (Iranian Journal of Nursing and Midwifery Research, 2016)
Background: Premature neonates′ feeding is of great importance due to its effective role in their growth. These neonates should reach an independent oral nutrition stage before being discharged from the Neonatal Intensive care Unit. Therefore, the researcher decided to conduct a study on the effect of palady and cup feeding on premature neonates′ weight gain and their reaching full oral feeding time interval. Materials and Methods: This is a clinical trial with a quantitative design conducted on 69 premature infants (gestational age between 29 and 32 weeks) who were assigned to cup (n = 34) and palady (n = 35) feeding groups through random allocation. The first feeding was administrated either by cup or palady method in each shift within seven sequential days (total of 21 cup and palady feedings). Then, the rest of feeding was administrated by gavage. Results: Mean hospitalization time (cup = 39.01 and palady = 30.4; P < 0.001) and mean time interval to reach full oral feeding (cup = 33.7 and palady = 24.1; P < 0.001) were significantly lower in palady group compared to cup group. Mean weight changes of neonates 7 weeks after the intervention compared to those in the beginning of the intervention were significantly more in palady group compared to the cup group (cup = 146.7 and palady = 198.8; P < 0.001). Conclusions: The neonates in palady group reached full oral feeding earlier than those of cup group. Subjects′ weight gain was also higher in palady group compared to the cup group. Premature neonates with over 30 weeks of gestational age and physiological stability can be fed by palady.